Handbook on advancements in smart antenna technologies for wireless networks - Sun, Chen, 1977-; Cheng, Jun, 1964-; Ohira, Takashi, 1955- (Information Science Reference, 2009)
"This book is a comprehensive reference source on smart antenna technologies featuring contributions with in-depth descriptions of terminologies, concepts, methods, and applications related to smart antennas in various wireless systems"--Provided by publisher.